DIGITAL POSSIBILITIES OF TELEVISION NEWS AND THEIR IMPLEMENTATION ON TRT AND RT (Proceedings of Southern Federal University. Philology, 2023)
DOI 10.18522/1995-0640-2023-4-220-229The study of the main vectors of the transformation of news television in the digital age showed that, turning into a hybrid platform, modern TV channels are undergoing significant changes affecting both the formats for collecting, organizing and presenting news content, and presenting it to viewers. The following parameters are distinctive of modern digital television: syndication and aggregation, vertical news feed format, active use of video with notes, structured news blocks, mailing lists and summaries, data visualization. These adjustments and changes involve a revision of the traditional concept of journalistic genres and a new approach to the formation of information through a change in linguistic and stylistic characteristics due to the new language of the media.Key words: digital television, digital technologies, content visualization, news stories, communication formats